2019
DOI: 10.1042/bsr20190681
|View full text |Cite
|
Sign up to set email alerts
|

N-acetylcysteine tiherapeutically protects against pulmonary fibrosis in a mouse model of silicosis

Abstract: Silicosis is a lethal pneumoconiosis disease characterized by chronic lung inflammation and fibrosis. The present study was to explore the effect of against crystalline silica (CS)-induced pulmonary fibrosis. A total of 138 wild-type C57BL/6J mice were divided into control and experimental groups, and killed on month 0, 1, 2, 3, 4, and 5. Different doses of N-acetylcysteine (NAC) were gavaged to the mice after CS instillation to observe the effect of NAC on CS induced pulmonary fibrosis and inflammation. The p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
3

Year Published

2020
2020
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 49 publications
2
22
3
Order By: Relevance
“…Accumulating evidence has indicated that silica induces inflammatory responses, including the secretion of inflammatory factors (26) and infiltration of inflammatory cells (27). In the present study, it was shown that in the silicosis group, total cell counts, as well as the neutrophil, lymphocyte and macrophage counts were high.…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…Accumulating evidence has indicated that silica induces inflammatory responses, including the secretion of inflammatory factors (26) and infiltration of inflammatory cells (27). In the present study, it was shown that in the silicosis group, total cell counts, as well as the neutrophil, lymphocyte and macrophage counts were high.…”
Section: Discussionsupporting
confidence: 50%
“…It reflects the quantities of oxidized free radicals in the body to a certain extent, and indirectly reflects the degree of oxidative stress, which is negatively correlated with lung function (34), and may lead to irreversible lung injury (27). Antioxidants, such as GSH-px and SOD, can not only resist the direct damage caused by oxidants, but also alters the course of inflammatory events associated with chronic lung diseases (27). In the present study, following exposure to silica, there was a significant decrease in GSH-px and SOD levels, as well as a significant increase in the levels of ROS and MDA in silicotic patients.…”
Section: Discussionmentioning
confidence: 99%
“…In a Cochrane review, patients with ARDS who were administered NAC spent less time in the ICU [ 46 ]. In animal models, NAC has been shown to have a protective effect against pulmonary fibrosis [ 47 , 48 ]. Currently, a clinical trial is being conducted on the effectiveness of NAC in critically ill patients with COVID-19 [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Anakinra, given to the 37-year-old man in a dose of 100 mg/day subcutaneously for 6 months, improved his respiratory functions, oxygen saturation, and inflammatory markers (C-reactive protein, erythrocyte sedimentation rate) [95]. Anti CD-11 antibodies [103] Agents influencing autophagy-lysosomal system Imipramine [104] Dioscin [105] Rapamycin/cAMP [106] Atractylenolide III [107] Trehalose [108] Antioxidants N-acetylcysteine [109][110][111] Corticosteroids Dexamethasone [112][113][114][115] Flunisolide [116] Endogenous glucocorticoids Annexin A1 [117] Agents increasing cAMP Roflumilast [118] Tadalafil [119] Sildenafil [115] Agents influencing TGFβ Emodin [120,121] Ponatinib [122] Table 1. Cont.…”
Section: Anti-cytokine Therapymentioning
confidence: 99%